2004
DOI: 10.1002/bies.20118
|View full text |Cite
|
Sign up to set email alerts
|

From modulator to mediator: rapid effects of BDNF on ion channels

Abstract: Neurotrophins (NTs) are [?AUTHOR] a family of structurally related, secreted proteins that regulate the survival, differentiation and maintenance of function of different populations of peripheral and central neurons.1,2 Among these, BDNF (brain-derived neurotrophic factor) has drawn considerable interest because both its synthesis and secretion are increased by physiological levels of activity, indicating a unique role of this neurotrophin in coupling neuronal activity to structural and functional properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
86
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 89 publications
0
86
0
1
Order By: Relevance
“…BDNF is also known www.chinaphar.com Xie H et al Acta Pharmacologica Sinica npg to be expressed and released in an activity-dependent manner in the central nervous system and can acutely modulate synaptic transmission and plasticity [40][41][42][43] . In a previous study, we and co-workers reported that BDNF is critical in the expression of L-LTP in the hippocampus suggesting that it is a key protein in long-term memory formation [44] .…”
Section: Critical Role Of Decreased Bdnf Expression In Chronic Intermmentioning
confidence: 99%
“…BDNF is also known www.chinaphar.com Xie H et al Acta Pharmacologica Sinica npg to be expressed and released in an activity-dependent manner in the central nervous system and can acutely modulate synaptic transmission and plasticity [40][41][42][43] . In a previous study, we and co-workers reported that BDNF is critical in the expression of L-LTP in the hippocampus suggesting that it is a key protein in long-term memory formation [44] .…”
Section: Critical Role Of Decreased Bdnf Expression In Chronic Intermmentioning
confidence: 99%
“…Akt signalling regulates the translation and transport of synaptic proteins in order to promote synaptic plasticity in learning and memory (Yoshii and Constantine-Paton, 2007). Along with the activation of TrkB, BDNF also triggers the opening of Na + gated ion channels, resulting in an influx of Ca 2+ and the enhancement of glutamate activation of N-methyl-D-aspartate (NMDA) receptors (Rose et al , 2004). NMDA receptors also play a crucial role in synaptic plasticity with their activation by glutamate leading to the induction of LTP Collingridge, 1993, Cooke andBliss, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tropomyosin receptor kinase B (TrkB, also known as NTRK2), as the high-affinity receptor for BDNF, are abundant in the nervous system and are crucial for synaptic plasticity in the CNS (Bramham and Messaoudi, 2005;Nagappan and Lu, 2005;Cohen and Greenberg, 2008). When activated by BDNF, TrkB receptors initiate three major signaling cascades, including those mediated by phosphoinositide 3-kinase (PI3K), phospholipase Cc (PLCc) and extracellular signal-regulated kinase 1 and 2 (ERK1/2; also known as MAPK3 and MAPK1, respectively) (Huang and Reichardt, 2003;Segal, 2003), thereby regulating synaptic transmission and membrane excitability in neurons (Poo, 2001;Rose et al, 2004).…”
Section: Introductionmentioning
confidence: 99%